The Development Of Recipe Management System (PRMS) - Nadia, Nasir (UTeM, 2008)
Recipe Management System (RMS) was developed for the use in the Fresh Department Store which will allow chef and the system administrator to manage the user and recipe management record. RMS is using Microsoft Visual Basic 2005 as the programming language and Oracle9i as the Database Management System (DBMS). The methodology that is used in the development of RMS is Iterative Waterfall Model and Structured System Analysis and Design Method (SSADM) as the database methodology. The methodology is used in making sure to develop RMS successfully. RMS is focusing on the role of the back end user as the system provides many features that were done by the Database Administrator (DBA). The System Administrator will be responsible as the role of DBA. The role of DBA that will be implemented in the RMS is to create new table, database backup and recovery, dynamic report creation, grant or revoke object or system privileges. Those features will be done through the interface of the RMS. As the other features provided by this system are to insert, update, delete and view user or recipe information and to change the value of quantity serve for the recipe. The expected output from the development of RMS is that this system will be used in the fresh department store.